Developing Environmental Services in Vietnam - Chu, Thi Mai Phuong (H. : ĐHQGHN, 2019)
In the current trend, human activities of production and activities have discharged a large amount of waste. This makes the pressure to handle environmental pollution increasing. Therefore, environmental services have become an important economic sub-sector of many countries including Vietnam. In Vietnam, as of 2017, have 3,769 enterprises operate in the field of environmental services. Of which, more than 80% are non-state enterprises, about 1% are FDI enterprises and the rest are state-owned enterprises. Enterprises mainly focus on services with high demand resulting from the requirements of the 2005 Law on Environmental Protection, such as designing, manufacturing, and building waste treatment systems; environmental monitoring and analysis; consulting, training, providing environmental information. This paper provides a general analysis of businesses operating in the environmental services industry, the situation of attracting FDI into the industry, pointing out the causes and shortcomings in the development of the industry and giving some discussions and recommendations for developing environmental services in Vietnam